Indoor environmental quality and occupant satisfaction in green-certified buildings. Issue 3 (3rd April 2019) - Altomonte, Sergio; Schiavon, Stefano; Kent, Michael G.; Brager, Gail
ABSTRACT: Green-building certification systems aim at improving the design and operation of buildings. However, few detailed studies have investigated whether a green rating leads to higher occupant satisfaction with indoor environmental quality (IEQ). This research builds on previous work to address this. Based on the analysis of a subset of the Center for the Built Environment Occupant Indoor Environmental Quality survey database featuring 11, 243 responses from 93 Leadership in Energy and Environmental Design (LEED)-rated office buildings, this study explores the relationships between the points earned in the IEQ category and the satisfaction expressed by occupants with the qualities of their indoor environment. It was found that the achievement of a specific IEQ credit did not substantively increase satisfaction with the corresponding IEQ factor, while the rating level, and the product and version under which certification had been awarded, did not affect workplace satisfaction. There could be several reasons for this, some of which are outside the control of designers and beyond the scope of rating systems based primarily on design intent. The challenges and priorities facing building professionals, researchers and green building certification systems are discussed for the creation of more comfortable, higher performing and healthier green-rated buildings.